Prevalence of common thrombophilia markers and risk factors in Indian patients with primary venous thrombosis - Mishra,Mahendra Narain (2010)
CONTEXT AND OBJECTIVE: Venous thrombosis occurs as a result of interaction of genetic and acquired factors including activated protein C resistance (APC-R), fibrinogen levels, antithrombin, protein C, protein S, lupus anticoagulants and anticardiolipin antibodies. This study was aimed at determining the prevalence of these common thrombophilia markers in Asian Indians with primary venous thrombosis. DESIGN AND SETTING: This was a cross-sectional study carried out in Mumbai. METHODS: Samples from 78 patients with a confirmed diagnosis of venous thrombosis and 50 controls were tested. Semi-quantitative estimation (functional assays) of protein C, protein S and antithrombin was performed. Quantitative estimation of fibrinogen was done using the Clauss method. Lupus anticoagulants were screened using lupus-sensitive activated partial thromboplastin time and β2-glycoprotein-I dependent anticardiolipin antibodies were estimated by ELISA. APC-R was measured using a clotting-based method with factor V deficient plasma and Crotalus viridis venom. Statistical analysis was performed using Epi-info (version 6). RESULTS: The popliteal vein was the most commonly involved site. Forty-four samples (56%) gave abnormal results. The commonest were elevated fibrinogen and APC-R (17.9% each), followed by low protein S (16.6%). CONCLUSIONS: This study confirms the literature findings that fibrinogen level estimation and screening for APC-R are important for the work-up on venous thrombosis patients since these, singly or in combination, may lead to a primary thrombotic episode. The frequency of the other thrombophilia markers was higher among the patients than among the controls, but without statistically significant difference.